Pengembangan Multimedia Interaktif Materi Zat dan Perubahannya pada Mata Pelajaran IPA Kelas VII SMP - Aina Syafiqa; Nofri Hendri; Ulfia Rahmi; Dedi Supendra (EduInovasi: Journal of Basic Educational Studies, 2026)
The limited ability of teachers to develop varied learning media and appropriate to the learning material causes science learning activities to only use simple media in the form of printed books and blackboards. As a result, in learning activities, students' learning responses tend to be passive, lack of enthusiasm for learning, quickly feel bored, have low concentration on the material presented and are lazy to read textbooks, some students often do other activities such as chatting, daydreaming, doodling on books, even disturbing friends. This research is a research & development that aims to develop and produce Interactive Multimedia material on Substances and Their Changes in the subject of science for class VII of junior high school. Using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation and Evaluation. The research subjects involved media experts, material experts and class VII students of SMP Negeri 8 Payakumbuh. Data collection instruments were observation, interviews, documentation and questionnaires. Data analysis techniques used descriptive analysis. The results of the study showed that the validation test by two media experts obtained a very feasible category with percentages of 97.77% and 96.66%, respectively. While the validation test by material experts showed a feasibility level of 100% with a very feasible qualification. The results of the practicality questionnaire showed a percentage of 93% with a very practical category. The effectiveness test using the N-Gain Score obtained a value of 0.84 with a high effectiveness category, marked by an increase in the average learning outcome from 50.4 in the pre-test to 91.17 in the post-test. It was concluded that the developed Interactive Multimedia was declared feasible, practical, and effective for use in addressing the problems of learning science on the topic of Substance and Its Changes at SMP Negeri 8 Payakumbuh.